1997
DOI: 10.1080/01635589709514581
|View full text |Cite
|
Sign up to set email alerts
|

DHA feeding provides host protection and prevents fibrosarcoma‐induced hyperlipidemia while maintaining the tumor response to araC in Fischer 344 rats

Abstract: Fischer 344 rats were inoculated with fibrosarcoma tumor cells and fed diets containing 5% or 10% (wt/wt) safflower oil or 10% oil containing docosahexaenoic acid (DHA). Animals were then treated with arabinosylcytosine (araC) or saline for six days. Tumor weights were highest in animals fed 10% safflower oil and treated with saline, intermediate in animals fed oil containing DHA and 5% safflower oil and treated with saline, and lowest in araC-treated animals from all diets. Plasma cholesterol and triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…The high level of DHA in liver and heart (11.5 %) in unsupplemented rats was likely due to a signiWcant endogenous synthesis of DHA from its precursor alpha-linolenic acid in these tissues [38]. These results are concordant with the previous studies [19,20]. Enrichment of normal cells or tissues with DHA or EPA alone (without chemotherapy) did not increase their susceptibility to oxidative stress [39][40][41].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The high level of DHA in liver and heart (11.5 %) in unsupplemented rats was likely due to a signiWcant endogenous synthesis of DHA from its precursor alpha-linolenic acid in these tissues [38]. These results are concordant with the previous studies [19,20]. Enrichment of normal cells or tissues with DHA or EPA alone (without chemotherapy) did not increase their susceptibility to oxidative stress [39][40][41].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the ubiquitous distribution of DHA, EPA [18][19][20], and chemotherapy to tissues, no additional toxicity to non-tumor tissues has been reported experimentally [6-9, 13, 21-25] or in patients [16,17]. This lack of toxicity to non-tumor tissues is not well understood.…”
Section: Introductionmentioning
confidence: 89%
“…Only a few studies have investigated the effect of DHA alone on body weight during chemotherapy. One study in healthy mice showed that DHA reduced body weight loss related to treatment with methotrexate (34), whereas 2 other studies showed an effect on body weight loss related to cytarabine neither in healthy rats (35) nor in rats bearing fibrosarcoma (36). In the present study, a diet enriched with DHA prevented body weight loss related to doxorubicin in rats bearing mammary tumors.…”
Section: Discussionmentioning
confidence: 47%
“…In vitro, DHA and/or EPA improve cytotoxic effects of several anticancer drugs [doxorubicin, epirubicin, paclitaxel, 5-fluorouracil, cytosine arabinoside (Ara-C), mitomycin, arsenic trioxide] toward various human cancer cell lines, including those of breast, colon, bladder, neuroblastoma, and glioblastoma [5][6][7][8][9][10][11][12][13]. In animal models, representing a variety of tumor sites, dietary supplementation with DHA and/or EPA in combination with chemotherapeutic drugs (Ara-C, doxorubicin, epirubicin, irinotecan, methotrexate) decreased tumor size [14][15][16], reduced side effects [17][18][19][20] and prolonged survival [21,22] (Table 1).…”
Section: Evidence That N-3 Pufa Can Improve the Response To Chemotherapymentioning
confidence: 99%